PENDAMPINGAN PENGGUNAAN MOLASSES DALAM MEMPERCEPAT PENGOLAHAN DAN PEMANFAATAN FESES TERNAK UNTUK PEMBUATAN PUPUK ORGANIK - Wijayanto, Adi (JPM Pambudi, 2018)
Very high fertilizer prices pose a very serious problem for farmers in Sumberdadi village, Bakung, Blitar, East Java, but this can actually be overcome with the available resources, but the knowledge and the community are very lacking on the information on fertilizer making. Therefore, to use livestock manure to be used as compost, it is necessary to conduct activities to start socialization and workshops on the use of molasses in accelerating the processing and utilization of animal feces for the manufacture of organic fertilizer. The method used in community service activities is the method of Participatory Action Research (PAR). The enthusiasm of the representatives of the community was very good, 85% of the community representatives invited to attend the event. The process of making organic fertilizer with molasses begins with the preparation of materials and tools needed. Molasses are good bacteria that are used to make compost. After organic fertilizer with a catalyst (bio-activator) molasses is made, then the next step is the implementation of the plant and eventually, it will be evaluated. Based on a five-day evaluation between rice that was given organic fertilizer with molasses it grew faster by an average of 1.5 cm compared to rice given an organic fertilizer with a length of 1.4 cm, whereas in the seeds of rice plants that were not given fertilizer at all the growth rate is around 1.2 cm. In corn kernels, there is a very significant difference between corn seeds which are given organic fertilizer and anorganic fertilizer compared to corn seeds without fertilizer at all.